Doubly Fed Induction Machine Models for Integration into Grid Management Software for Improved Post Fault Response Calculation Accuracy—A Short Review - Andrija Mitrovic; Luka Strezoski; Kenneth A. Loparo (Energies)
With the escalating proliferation of wind power plants, the imperative focus on system robustness and stability intensifies. Doubly fed induction machines (DFIMs) are extensively employed in land-based wind power plants due to their performance advantages. While the stator windings are directly connected to the power system, the rotor windings are connected via power converters, making these units vulnerable to voltage disturbances. During faults, voltage drops at the stator terminals lead to elevated voltages and currents on the rotor side due to electromagnetic coupling between stator and rotor, potentially damaging rotor insulation and costly power electronics. Historically, wind power plants employing DFIMs were disconnected from the grid during faults—an unsatisfactory solution given the burgeoning number of these installations. Consequently, grid operators and IEEE standard 2800 mandate fault ride-through (FRT) capabilities to maintain system stability during disturbances. This paper provides a short review of the existing techniques for protecting DFIMs during faults, focusing on both passive and active protection methods. Additionally, a simple calculation is presented to compare two different protection strategies, illustrating the differences in their effectiveness. The review emphasizes the necessity for developing models that represent all protection methods for DFIMs, due to the clear differences in the results obtained.